Molecular assessment of heterotrophy and prey digestion in zooxanthellate cnidarians. Issue 15 (9th October 2013) - Leal, M. C.; Nejstgaard, J. C.; Calado, R.; Thompson, M. E.; Frischer, M. E.
Abstract Zooxanthellate cnidarians are trophically complex, relying on both autotrophy and heterotrophy. Although several aspects of heterotrophy have been studied in these organisms, information linking prey capture with digestion is still missing. We used prey‐specific PCR‐based tools to assess feeding and prey digestion of two zooxanthellate cnidarians – the tropical sea anemone Aiptasia sp. and the scleractinian coral Oculina arbuscula. Prey DNA disappeared rapidly for the initial 1–3 days, whereas complete digestion of prey DNA required up to 10 days in O. arbuscula and 5 or 6 days in Aiptasia sp. depending on prey species. These digestion times are considerably longer than previously reported from microscopy‐based examination of zooxanthellate cnidarians and prey DNA breakdown in other marine invertebrates, but similar to prey DNA breakdown reported from terrestrial invertebrates such as heteroptera and spiders. Deprivation of external prey induced increased digestion rates during the first days after feeding in O. arbuscula, but after 6 days of digestion, there were no differences in the remaining prey levels in fed and unfed corals. This study indicates that prey digestion by symbiotic corals may be slower than previously reported and varies with the type of prey, the cnidarian species and its feeding history. These observations have important implications for bioenergetic and trophodynamic studies on zooxanthellate cnidarians.